Learning experience in dynamic and non-dynamic curriculum sequencing systems : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Information Technology at Massey University - Katuk, Norliza (Massey University, 2012)
This PhD thesis presents a series of interrelated studies about computer-based learning experience with a focus on a dynamic curriculum sequencing system (DCSS). A DCSS is an adaptive computer-based system that organises learning material dynamically, based on the learners’ learning parameters such as prior knowledge, learning styles and preferences. The learning experience refers to the learners’ cognitive engagement during their interactions with computer-based systems. It is important to note that the learning experience discussed here is reviewed in the context of the flow theory. Many previous studies have claimed that learners’ psychological well-being and future use of computer-based learning are correlated with their learning experiences. Hence, this thesis provides some empirical evidence about the DCSS learning experience to complement the existing literature in the area of computer-based learning. The thesis intends to achieve two main objectives. First, it aims to identify whether or not the DCSS learning experience is significantly different in comparison to the non-DCSS (i.e., a recommendation system). Additionally, it intends to examine whether the DCSS and the non-DCSS learning experiences change over time. It also develops and validates a new technique that can improve the DCSS learning experience, known as a skill-challenge balancing (SCB) technique. In order to achieve the first objective, two experimental studies were conducted using two types of computer-based systems (i.e., the DCSS and the non-DCSS) for teaching ‘Computer Networks’. The self-reporting technique was employed to measure the learning experiences in both studies. For the second objective, the software analysis and design tasks were performed to visualize the SCB technique conceptually and technically. It was followed by an experimental study that validates the new technique using the same methodological approach as in the first two studies. The first two experimental studies suggested that the DCSS and the non-DCSS gave the learners different learning experiences. These studies further identified the learners’ cognitive states showing some of them suffered from boredom and anxiety in particular learning conditions. The findings of these studies emphasized that there is a need for a novel approach to maintain learning experience in computer-based learning. For this reason, this thesis also proposes a new learning experience monitoring technique (i.e., the SCB) considering some underlying principles from the flow theory. This technique was empirically validated to be effective in improving the DCSS learning experience. As computer-based learning is an essential tool in current higher educational settings, the outcomes of this thesis are discussed in relation to adaptive design of computer-based learning and human-computer interaction.
Keywords: Dynamic curriculum sequencing system; Computer-based learning; Computer-assisted learning; Computer-assisted instruction; Learning styles; Skill-challenge balancing; Software analysis; Learning techniques